Toward a holistic networks approach to strategic third-party intervention: A literature review. (September 2019) - Hannigan, Colin
How do third parties decide to intervene in civil conflicts? The study of intervention has focused primarily on the conflict characteristics and dyadic linkages that make intervention more likely, or the conflict outcomes that interventions generate, while holding all else equal. To paint a more complete picture of what goes into the intervention decision, I advocate a shift in the way we conceive of interventions toward network analysis, which grants due agency to the multiple external actors and internal combatants that influence the decision to intervene. This review critically examines and synthesizes the recent literature on third-party interventions in civil conflict and, in so doing, identifies some areas for future research.